PSV-21 Treatment of composted poultry litter with natural hop extracts, effects on Salmonella, Escherichia coli and nitrogen. (7th December 2018) - Ruiz-Barrera, O; Arzola-Alvarez, C; Castillo-Castillo, Y; Corral-Luna, A; Anderson, R; Hume, M; Nisbet, D; Flythe, M; Salinas-Chavira, J; Portillo, M
Abstract: Poultry litter is a potentially valuable crude protein feedstuff for ruminants but must be treated to kill pathogens before feeding. Composting effectively kills pathogens but risks losses of ammonia during uric acid degradation. Presently, 250-g portions of used wood chip litter (WCL, 73% dry matter) were treated with 125 mL 0.4 M phosphate buffer (pH 6.5) containing Chinook or Galena hop extracts to achieve 0.03 g beta-acid/g WCL. Control WCL was treated with buffer alone. The WCL was distributed (11 g) to 50-mL tubes (3 tubes/treatment per sampling day), inoculated with a marked challenge strain of Salmonella Typhimurium (ST) then capped and incubated at successive 3-day increments at 22 o C, 37 o C and 42 o C. Repeated measures analysis of variance of ammonia, urea and uric acid measured in samples collected on days 0, 3, 6 and 9 revealed a main effect of day on uric acid ( P < 0.05), which increased from day 0 to 3 (a high of 9.4 µmol/g) and declined thereafter to its low (4.1 µmol/g) on day 9. A day x treatment interaction was observed ( P < 0.05) on ammonia accumulations which increased steadily, accumulating more on day 9 with Galena hops-treated WCL than with control- or Chinook hops-treated WCL (7.3, 6.6 and 5.6 µmol/g, respectively). A main effect of treatment but not day or their interaction was observed on urea accumulations, highest for control, lowest for Galena- and intermediate for Chinook hops-treated WCL (1.7, 0.5 and 1.0 µmol/g, respectively). Analysis of bacterial concentrations revealed little effect of treatment on bacterial counts; however, main effects of day on ST and E. coli were observed ( P < 0.05) with both being decreased below detection limits (1 log10 CFU/g) by day 9. These results indicate that composting combined with Chinook hops-treatment may help safely preserve crude protein of WCL.